Association between the absence of colostrum feeding and symptoms of intestinal obstruction or neonatal necrotizing enterocolitis - Hananto Wiryo; M. Hakimi; A. Samik Wahab; Pitono Soeparto (Paediatrica Indonesiana, 2004)
Objective To assess the relationship between withholding colos-trum and symptoms of intestinal obstruction (SIO) or neonatal ne-crotizing enterocolitis (NNEC).Methods This was a longitudinal cohort study in four subdistrictsin West Lombok involving mothers and live newborns. Motherswere interviewed about prenatal care, delivery process, and prac-tice of colostrum feedings. Neonates were followed everyday for28 days by field assistants for signs of intestinal obstruction orNNEC. We used X 2 test to analyze the association between theabsence of colostrum feeding and the occurence of SIO and stu-dent t test to compare the average of colostrum feeding betweenthe SIO and the non-SIO group.Results 3420 live newborns between 1993-1994 were observed.1900 mothers gave colostrum while 1520 did not. The incidence ofSIO was 1.8%. There was a significant association between theabsence of colostrum feeding and the occurence of the SIO (RR1.816; 95%CI 1.08-3.06; p=0.028). No infants with NNEC weregiven colostrum.Conclusion The absence of colostrum feeding is an importantrisk factor for the occurence of SIO and NNEC in neonates